Ego resiliency and the condition of health - Dolińska-Zygmunt, Grażyna; Włodarczyk, Małgorzata (Polish Journal of Public Health, 2011)
Introduction. Increasing interest in factors disturbing health has resulted in numerous discoveries connected with theoretical basis of health disorders and also to individual resources, which protect a person against many different stressors. One of them is ego resiliency form J.J. Blocks’ concept and this publication aims to present adaptive features of ego resiliency. Aim. The aim of this study was to examine adaptive function of ego resiliency by analysing Ego Resiliency Scale-ER89 (J.Block, 1996) results of girls and women with health disorders. The Scale underwent the process of cultural adaptation and its reliability was measured with the result α=0,719 for a sample of women with health disorders and with the result α=0,45 for women without health disorders. Material and methods. The research comprised 110 women, aged 15-30. The criterion of participation was their health condition. The group of 60 persons without any health disorders consisted of: female students from junior high school, aged 15-17; university female students, aged 19-25 and women, aged 26-30. The group of 50 women with health disorders consisted of: 18 women with anorexia, aged 15-25; 17 women with depressive disorders, aged 21-26 and 15 women with neurotic disorders, aged 20-30. Results. Independent samples t-Test and multivariate analysis of variance (MANOVA) showed that the women with anorexia, depressive and neurotic disorders have lower level of ego resiliency than the women without health disorders, what may indicate their general difficulties in adaptation. Conclusions. There are significant differences between the women with health disorders and the healthy women in their level of ego resiliency. The women with diagnosed anorexia, depression or neurotic disorders tend to have lower ego resiliency than the women without any health disorders.